Sharia and Islamic state in Indonesia constitutional democracy: an Aceh experience - Khamami Zada (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2023)
A question arises in the implementation of Sharia in Aceh: Is Sharia compatible with democracy as a political system in Indonesia? And with a comprehensive Sharia implementation, will it threaten the existence of the Indonesian state? This paper discussed Sharia's expansion, potentially leading to the establishment of the Islamic state of Aceh. This study was conducted using qualitative research. Primary data were taken from interviews with academics, journalists, non-governmental organization activists, youths, and focused group discussions with the leaders of the Islamic Sharia Office in Aceh Province. Meanwhile, the secondary data were gathered from historical documents, legislation, and Qanun in Aceh. The collected data were analyzed using the legal history theory of Pound (1923) and the Islamic democratic state theory of Hayes (2014). This research found the gradual implementation of Sharia in Aceh within the Indonesian democratic system. These constitutional ways were chosen to avoid the conflict between the Sharia and national legal and political systems. This, then, has led to the legalization of Sharia in the local and national political contestation. In the next phase, with the increasingly widespread Sharia rules and regulations on worship, criminal law, and economic law, Aceh can be called a small prototype of an Islamic state. With the significant historical, political, and social power, the roadmap of Sharia implementation in Aceh indicates a clear direction for the reflection of God's sovereignty as the foundation of the Islamic democratic state, even if it is in the local context.